Infinite products of resolvents of accretive operators - Reich, Simeon; Zaslavski, Alexander J. (Topological Methods in Nonlinear Analysis, 2000)
We study the space M_m of all m-accretive operators on a Banach space X endowed with an appropriate complete metrizable uniformity and the space M^*_m which is the closure in M_m of all those operators which have a zero. We show that for a generic operator in M_m all infinite products of its resolvents become eventually close to each other and that a generic operator in M_m^* has a unique zero and all the infinite products of its resolvents converge uniformly on bounded subsets of X to this zero.